G290(P) Respiratory complications following tracheo-oesophageal fistula (TOF) repair. (25th October 2020) - Akbar, S; Thomson, L
Abstract : The awareness of respiratory complications post TOF repair is variable. Due to abnormal airway epithelium and impaired muco-ciliary clearance, this group are vulnerable to lower respiratory tract infections (LRTIs) and recurrent wheezing which can lead to bronchiectasis if left untreated. To evaluate respiratory complications in this vulnerable group of patients, a retrospective analysis of patients diagnosed with TOF between 2009 and 2019 was carried out in a tertiary centre. Patients up to the age of 16 years of age who remained under local paediatric follow-up were included in analysis. A total of 36 patients were identified. 61% were male with a mean age of 7.2 years (range 1.9 to 15.3 years). The average age of respiratory referral was 2.79 years with cough the commonest reason (table 1 ). The referrals came from multiple sources as outlined in table 2 . Tracheomalacia was diagnosed in 9/36 (25%), asthma in 6/36 (17%) and VIW in 2/36 (6%) patients. The average number of chest x-rays in the first month of life was 9.8. 7 patients had more than 10 performed. In this group, there was a higher incidence of paediatric respiratory problems with 4 admissions to PICU requiring non-invasive support for LRTIs or acute wheeze. Moreover, there were 10 hospital admissions with LRTIs in this group compared with 15 in the whole group. Only 1 child was extremely preterm (born less than 28 weeks' gestation) and 1 had a diagnosis of chronic lung disease, suggesting this group was at increased risk for TOF complications rather than prematurity. It is important that health professionals who follow-up patients are aware of the respiratory complications of TOF and need for close monitoring and referral.